Peran Mahasiswa KKN Dalam Mengurangi Konflik Sosial Berbasis Agama Di Desa Lokasi Baru - Saepudin Saepudin; Dwi Indah Lutfiatin; Reni Kristinawati; Ismail Adi Nugoro; M. Habib Pratama; Veronika Lestari; Ella Astuti; Amelia Anggita; Sopi Amalia; Atika Putriana; Aqilah Luthfiyah Khansa (Pakis Journal Institute, 2024)
The formation of a harmonious society requires a moderate attitude in each individual community based on religious values. Many conflicts that occur are not caused by differences, but are caused by an interest based on personal interests. Religion always teaches us to be moderate, which we must do because it is absolute. Indonesia with its diversity of ethnicity, culture, race and religion also requires people to be moderate. Conflicts are generally triggered by personal interests, then not addressed with a strong religious understanding will become a prolonged conflict. Every religion commands us to avoid extremes. This research proves that it is the pattern of community interaction that triggers conflict, where poor community interaction is due to the non-implementation of religious values in the interaction. This is not due to the wrong religious teachings, because from the Islamic perception described in the Qur'an, there is nothing that explains that humans are extreme. The Qur'an commands fairness and moderation. The same thing is also explained in Al-Kitab. As for preventing conflict, there are four ways through community empowerment. This research uses a qualitative approach method obtained from interviews as primary data. Then, the fulfilment of secondary data is done through literature review.